(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
In the article, the authors consider various approaches to defining the concept of “spirituality”. It is noted that the concept of “spirituality” is one of the most difficult definitions in philosophy due to the ambiguity of semantic content. The essence of the concept of “spirituality” varies depending on the subject of study of the scientific discipline. The authors consider philosophical, cultural, sociological, aesthetic, anthropological, and psychological approaches to defining this concept. Biological, cosmocentric, idealistic, materialistic views of thinkers are also considered. The authors paid great attention to Soviet and Russian researchers when determining the essence of the concept under consideration. It is noted that the main elements of the spiritual sphere of society as a defining system are the unity of spiritual production, spiritual needs, values, and relationships. In conclusion, it is concluded that spirituality is the unifying principle of society, expressed in the form of moral values and reflected in the concept of “conscience”.